GREEN TOURISM IN THE CONTEXT OF CLIMATE CHANGE TOWARDS SUSTAINABLE ECONOMIC DEVELOPMENT IN THE SOUTH ASIAN REGION - AZAM, Mehdi; SARKER, Tapan (Journal of Environmental Management and Tourism; Vol 2 No 1 (2011): JEMT Volume II Issue 1(3) Summer 2011, 2011)
This paper attempts to examine the environmental consequences and challenges of tourism development in developing economies with particular focus on the South Asian region. South Asia is home to one-third of the world’s population and is experiencing a rapid growth in tourism due to its unique cultural and natural resources. The industry is not only dependant on the natural environment, but also can significantly alter it, meaning many tourist destinations are highly vulnerable to the impacts of climate change. These problems mean that developing nations need to take measures to control tourism in order to ensure the sustainability of the environment, but are limited by their weak institutional framework,, political instability and inegalitarian social and economic structures. This paper suggests a more effective environmental governance mechanism through incorporating eco-thinking initiatives and climate change as a management challenge in order to foster the development of eco-tourism.